Crime, correction, education and welfare in the U.S. – What role does the government play? - Hazra, Devika (369 EGFR SIGNALING IMPAIRS THE ANTIVIRAL ACTIVITY OF INTERFERON-ALPHA, 2022)
As federal, state and local governments continue to allocate a significant share of their resources to law enforcement and correctional spending, concerns have risen that spending in education and welfare is declining. With fiscal pressure in the United States mounting, it is important to determine the effectiveness of public spending in deterring crime. This paper compares the effectiveness of the impact of government spending on welfare and education with that of law enforcement and correction on crime. Using panel data from 50 U.S. states over a time period of 1994–2014, results of linear regression with panel corrected standard errors as well as GMM estimation reveals that public welfare and education spending can potentially lower violent and property crime rates but law enforcement spending can only deter property crime. However, correctional spending can exacerbate both types of crimes. There is little to no evidence of the presence of crowding out of one category of spending by another. This results in the policy implication that more resources be allocated towards welfare and education programs.